Lethal franchise: The evolution of the Torrente saga (1998–2011). Issue 3 (1st September 2014) - Jordan, Barry
The so-called Torrente saga (1–4, 1998–2011), written, directed and partly co-produced by Santiago Segura, has become the most commercially successful franchise in Spain's entire film history. With four instalments to date (and a fifth now scheduled for release in October 2014), these trash comedy films have so far attracted over 14.5 million local admissions and over 71 million euros in domestic box office, not counting ancillary revenues (source mcu.es). Compared to dominant, taxpayer-subsidized, art film productions, which evoke very little spectator appeal and remain almost entirely loss making, Segura's audiences and grosses constitute outstanding, indeed unique, commercial achievements. In this article, my main aim is to explain why the Torrente franchise has been so popular and consistently successful, at least in Spain (though much less so internationally). At the same time, given that the Torrente phenomenon reflects important developments taking place in the marketing, exhibition and consumption of recent Spanish cinema, this article will explore the franchise as a case study of these changes.